Réponses

  • Utilisateur Brainly
2014-05-20T06:40:43+02:00
Bonjour, 

f(x) = 2x² - 12x + 10


2(x - 3)² - 8
= 2(x² - 6x + 9) - 8
= 2x² - 12x + 18 - 8
= 2x² - 12x + 10
= f(x)

2(x - 1)(x - 5)
= 2(x² - 5x - x + 5)
= 2x² - 10x - 2x + 10
= 2x² - 12x + 10
= f(x)

Bonne journée! =)
2014-05-20T08:36:13+02:00
Bonjour
f(x)= 2x²-12x+10  
1)
2(x - 3)² - 8 
2(x² - 6x + 9 ) - 8 
2x² - 12x + 10  ce qu'il fallait démontrer 
on voit que f(x) aura son miimum = - 8   pour x = 3
2)
f(x) = 2(x - 1)(x - 5) 
f(x) = 2(x² - 5x - x + 5)
f(x) = 2x² - 12x + 10   
on voit que 
f(x) = 0  pour x = 1  ou x = 5 
Bonne journée